Đơn giản các bt sau
(7x-4)×(2x+3)-13x
a^3-(a^2-3a) ×(a+3)
(2a-b) ×(b+4a) +2a×(b-3a)
5b×(2x-b) +(x-6a) ×(5a+2x )
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(7x-4\right)\left(2x+3\right)-13x\)
\(=14x^2+21x-8x-12-13x\)
\(=14x^2-12\)
\(a^3-\left(a^2-3a\right)\left(a+3\right)\)
\(=a^3-\left(a^3+3a^2-3a^2-9a\right)\)
\(=a^3-a^3-3a^2+3a^2+9a\)
\(=9a\)
\(\left(2a-b\right)\left(b+4a\right)+2a\left(b-3a\right)\)
\(=2ab+8a^2-b^2-4ab+2ab-6a^2\)
\(=\)\(2a^2-b^2\)
\(5b\left(2x-b\right)+\left(x-6a\right)\left(5a+2x\right)\)
\(=10bx-5b^2+5ax+2x^2-30a^2-12ax\)
\(=2x^2-30a^2-5b^2+10bx-7ax\)
<=>9*(a+b) ^2-(a+b)
<=> (a+b) *(9*(a+b) -1)
<=> (a+b )*(9a+9b-1)
\(A=4x^2-12x+11\)
\(A=4x^2-12x+9+2\)
\(A=\left(2x-3\right)^2+2\)
Nhận xét: \(\left(2x-3\right)^2\ge0\forall x\)
\(\Rightarrow\left(2x-3\right)^2+2\ge2\forall x\)
Dấu "=" xảy ra \(\Leftrightarrow\left(2x-3\right)^2=0\Rightarrow x=\frac{3}{2}\)
Vậy \(minA=2\Leftrightarrow x=\frac{3}{2}\)